Simulating the integration of original equipment manufacturers and suppliers in fractal environment. (1st January 2012) - Saad, Sameh M.; Aririguzo, Julian C.
The Fractal Manufacturing Partnership (FMP) is a new manufacturing strategy, whereby Original Equipment Manufactures (OEMs) go into close relationship with their key suppliers and the latter become assemblers of their modular components with heightened sense of responsibility while sharing and co-owning the OEMs' facility. The key objective of this relationship is to maximise the ability to respond swiftly and robustly to changes in the environment. In this paper, the integration of OEM and key suppliers is modelled and simulated to articulate key factors that are critical in this partnership and quantifying and harnessing the direct benefits of this new approach.